2013
DOI: 10.1002/dc.23023
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathologic diagnosis on joint lavage fluid for patients with temporomandibular joint disorders

Abstract: Temporomandibular joint (TMJ) disorders (TMD) are usually diagnosed based on the patient's clinical findings and the results of image investigations; however, understanding of the inflammatory process in TMJ is difficult. In addition, many of the TMJ disease types share common principal symptoms. Therefore, TMJ diseases in the early stage can be misdiagnosed with TMD. It is hypothesized that cytopathologic examination of the joint lavage fluids is useful in interpreting the TMD-associated inflammatory process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The neutrophil is the first immune cell to enter into inflamed tissues and it has been associated with the development and chronicity of inflammatory diseases, such as TMD (Mikami et al, 2014). Also, leukocytes are present in the joint fluid of approximately 50% of patients with TMD (Mikami et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutrophil is the first immune cell to enter into inflamed tissues and it has been associated with the development and chronicity of inflammatory diseases, such as TMD (Mikami et al, 2014). Also, leukocytes are present in the joint fluid of approximately 50% of patients with TMD (Mikami et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil is the first immune cell to enter into inflamed tissues and it has been associated with the development and chronicity of inflammatory diseases, such as TMD (Mikami et al, 2014). Also, leukocytes are present in the joint fluid of approximately 50% of patients with TMD (Mikami et al, 2014). Moreover it has been shown that ATP released in an inflamed joint, via P2X7 receptor activation, induces articular hyperalgesia that depends on neutrophil migration (Teixeira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As regional specialist surgeons, these specialist treat the entire cranio‐maxillo‐facial anatomical complex, that is: the mouth, jaws, face, skull, as well as associated soft tissue structures. As such, they may perform FNA and other biopsies of lumps and bumps as needed, but conventional cytology may also be utilized for the study of synovial fluid or lavage fluid from the temporo‐mandibular joints . How often most of us examine a bony or soft tissue tumor of the skull, as part of our routine head and neck cytopathology practice, as opposed to our colleagues in orthopedic cytopathology depends on local circumstances.…”
mentioning
confidence: 99%